Antibody persistence and immune memory 4 years post-vaccination with combined hepatitis A and B vaccine in adults aged over 40 years - Chlibek, Roman; von Sonnenburg, Frank; Van Damme, Pierre; Smetana, Jan; Tichy, Petr; Gunapalaiah, Bhavyashree; Leyssen, Maarten; Jacquet, Jeanne-Marie (Journal of travel medicine, 2011)
Persistence of immune response was assessed in adults aged >40 years (N = 596) following primary vaccination with combined hepatitis A/B vaccine or concomitant monovalent hepatitis A and B vaccines. Anti-hepatitis A virus antibody responses persisted for at least 4 years regardless of the vaccine used, with anti-hepatitis B surface antibody responses higher and more sustained in subjects who received the combined hepatitis A/B vaccine. Response rates to an additional dose of the same vaccine(s) used for priming were high.
Keywords: Immunologic Memory; hepatitida B; sekundární imunizace; Hepatitis A Antibodies; Hepatitis A; hepatitida B - protilátky; Immunization, Secondary; Middle Aged; mužské pohlaví; Hepatitis B Antibodies; Adult; kombinované vakcíny; Hepatitis A Vaccines; Hepatitis B; hepatitida A - protilátky; ženské pohlaví; vakcína proti hepatitidě A; Humans; Vaccines, Combined; lidé středního věku; imunologická paměť; vakcína proti hepatitidě B; dospělí; Female; Hepatitis B Vaccines; hepatitida A; lidé; Male